2010
DOI: 10.1002/pssc.201000446
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic and photoconductivity characteristics of (a‐C:Fe)/Al2O3/Si structure

Abstract: The iron‐doped amorphous carbon films (a‐C:Fe) and Al2O3 films were deposited on n‐type silicon substrates using pulsed laser deposition to form (a‐C:Fe)/Al2O3/Si structures. The Fe diffused into a‐C films by annealing treatment and formed Fe‐doped amorphous homogeneous structure. The a‐C:Fe films are disordered graphitized carbon system and are rich in sp2. The results show that these junctions have good rectifying properties and great Photovoltaic (PV) effect and photoconductivity (PC). PV parameters of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The peak positions of the G band of all the samples are about 1570~1580 cm -1 . Furthermore, according to the relation between sp 2 contents and band gaps [7], the band gaps of all films are estimated to be less than 1.0 eV. Previous studies showed that the natural SiO 2 film formed in the air is non-crystal structure and its thickness is approximately between 2 nm [ 1].…”
Section: Microstructure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The peak positions of the G band of all the samples are about 1570~1580 cm -1 . Furthermore, according to the relation between sp 2 contents and band gaps [7], the band gaps of all films are estimated to be less than 1.0 eV. Previous studies showed that the natural SiO 2 film formed in the air is non-crystal structure and its thickness is approximately between 2 nm [ 1].…”
Section: Microstructure Analysismentioning
confidence: 99%
“…With excellent performance in electrical, chemical and mechanical properties, new carbonaceous materials such as amorphous carbon,carbon nanotubes, graphene and fullerenes have attractive application prospects in microelectronic devices,optoelectronics and so on [1][2][3][4][5]. Among them, the amorphous carbon is the earliest successful carbon-based semiconductor to be studied in solar cell.Many research groups have successfully obtained a-C/Si heterojunction solar cells by pulsed laser deposition(PLD),magnetron sputtering and chemical vapor deposition [1,2,6,7], and some of the a-C/Si heterojunction solar cells have good performances.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous carbon (a‐C), a disordered structure of carbon forms, has stimulated a lot of research interest due to its variable network of sp 3 , sp 2 , and sp 1 hybrid bands 1. The a‐C materials, with their excellent mechanical, chemical, electrical, and optical properties, have been applied in many different fields, such as solar cells 2, 14–18, sensors 3–6, protective coating 7, and so on. In addition, due to the advantages of stability and low cost, the a‐C film shows great potential to substitute traditional Si and Mo materials for use in electronic devices 1.…”
Section: Introductionmentioning
confidence: 99%
“…First, the bandgap of a‐C film can be controlled in a relatively wide range of 0.2–3 eV by controlling the dose of doping or structures (e.g., sp 3 /sp 2 ratio, cluster size). Until now, a lot of work has been done to fabricate a‐C film/Si structure photovoltaic devices, in which the a‐C film was doped by B 14, P 16, I 2, Fe 17, N 18. Our group have successfully fabricated a a‐C:Pd film/SiO 2 /Si heterojunction solar cell, which shows an open‐circuit voltage ( V oc ) of 0.33 V, a short‐circuit current density ( J sc ) of 3.5 mA/cm 2 and a conversion efficiency ( η ) of 4.7% under light illumination of 15 mW/cm 2 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation